Metaphorical conceptualization of the coronavirus in English and Russian media discourse - Mirjana Adamović; Maja Stevanović (Opera slavica, 2025)
Against the background of cognitive linguistics theory which includes the analysis of conceptual metaphors in discourse, in this paper we analyze two metaphorical scenarios—the WAR scenario and the NATURAL DISASTER scenario which frame the conceptualization of the coronavirus and concepts closely related to the coronavirus pandemic in English and Russian media discourse. Based on the corpora of metaphorical expressions excerpted from various media sources, the aim of this paper is to illustrate the cross-cultural universality of the conceptual mappings and shed light on the potential reasons for the emergence of the given metaphorical scenarios in conceptualisation.